Soil water distribution and simulation under subsurface drip irrigation in cotton (Gossypium hirsutum) - NASRABAD, GHORBAN GHORBANI; RAJPUT, T B; PATEL, NEELAM (The Indian Journal of Agricultural Sciences, 2013)
To see the effect of salinity of irrigation water under subsurface drip irrigation on cotton (Gossypium hirsutum) yield, a field experiment was conducted on loamy soils at Precision Farming Development Center, Water Technology Center, IARI, New Delhi, during 2009 and 2010 kharif. Irrigation water having four levels of salinity (EC1= 2 dS/m (ground water), EC2.= 5 dS/m, EC3= 8 dS/m and EC4=11 dS/m) taken as main plot treatment was used as drip with laterals placed at three depths (at the surface, 15 cm and 30 cm below the soil surface) as sub-plot treatments in a split plot design with three replications. The results indicated that cotton yields were not influenced by irrigation water salinity up to 8 dS/m and different lateral depths during two years but decreased by 37.3, 44.3 and 36.0% in 2009 year and 26.6, 35.1 and 42.2 % in 2010 years at 11 dS/m as compared with EC1, EC2 and EC3 treatments, respectively. Distribution of soil moisture data showed a horizontal decrease in soil water content at a distance of 20 and 40 cm away from drip line and vertical soil depths. Distribution of soil moisture was simulated by Hydrus 2D model. The model evaluated by AE and RMSE showed a good correspondence on soil water distribution between observed data from field experiment and simulated by model. The AE ranged from –0.015 to –0.002 and RMSE from 0.003 to 0.015.